Influência das características da aeração de uma válvula loop seal no rendimento operacional do ciclone de um leito fluidizado circulante - Pecete, Andrel de Souza (2023)
Cyclones are devices widely used in industrial processes to separate solid particles from streams of fluids. In applications involving Circulating Fluidized Bed (CFB) furnaces, cyclones ensure a stable furnace operation by preventing inert particles and material from leaving the system early. The experimental assessment of cyclone performance coupled to CFB pilot units has been scarcely explored, and the relationship between cyclone separation efficiency and aeration flow rate is still unknown. Furthermore, the literature shows that, under some operating conditions, a fraction of the aeration flow rate applied to the solids recirculation valve (loop seal) could take the opposite direction to that expected, affecting the cyclone operation. However, these studies do not feature any data regarding the influence of this phenomenon on the separator´s performance. Given this gap, this work proposed to experimentally determine the influence of both the flow rate and the aeration position on the collection efficiency and pressure drop of a cyclone coupled to a CFB system operated under room conditions with different levels of solids inventory. The experiments were carried out in a cold flow fast fluidization unit, keeping the fluidizing gas velocity constant and the mean particle size fixed. The analysis included determining the statistical significance of the effects produced by the experimental conditions on the cyclone operation, based on a 23 factorial design run in duplicates, in which only were considered the maximum and minimum values of each controlled variable. The results showed that the aeration flow rate is inversely proportional to the cyclone's collection efficiency. This effect is even more significant when using a lower solids inventory. On the other hand, changing the aeration position did not cause a significant variation in the cyclone's collection efficiency. In addition, the static pressure profile, the pressure drops in the CFB system and the solids circulation flow did not undergo significant variation with the change in the aeration flow rate, suggesting no interaction among these variables during the tests. Unlike the cyclone collection efficiency, the pressure drop in the cyclone changed only with the level of solids inventory used. The results of this study suggest that, under operational conditions similar to those analyzed here, in which the variation in the aeration flow rate does not cause alteration in the solids recirculation flow and the solids inventory remains relatively low, the performance of the cyclone can be significantly influenced, affecting the efficiency of a CFB furnace.